2007
DOI: 10.1523/jneurosci.5188-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential Spatial Representation of Taste Modalities in the Rat Gustatory Cortex

Abstract: Discrimination between foods is crucial for the nutrition and survival of animals. Remarkable progress has been made through molecular and genetic manipulations in the understanding of the coding of taste at the receptor level. However, much less is known about the cortical processing of taste sensation and the organizing principles of the gustatory cortex (GC). Using genetic tracing, it has recently been shown that sweet and bitter taste are processed through segregated neuronal circuitries along the gustator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
175
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(202 citation statements)
references
References 55 publications
24
175
1
2
Order By: Relevance
“…These anatomical findings indicate that the area corresponds to the secondary somatosensory cortex (S2) and oral region of the IC (IOR), as reported by Nakamura et al (49). S2/IOR receives varied somatosensory information from oral regions, including PDL sensation, gustation (50)(51)(52), and nociception (49,53,54). Interestingly, electrical stimulation of S2/IOR induces rhythmic jaw movement (55,56).…”
Section: Cortical Responses To Pdl Stimulationsupporting
confidence: 70%
“…These anatomical findings indicate that the area corresponds to the secondary somatosensory cortex (S2) and oral region of the IC (IOR), as reported by Nakamura et al (49). S2/IOR receives varied somatosensory information from oral regions, including PDL sensation, gustation (50)(51)(52), and nociception (49,53,54). Interestingly, electrical stimulation of S2/IOR induces rhythmic jaw movement (55,56).…”
Section: Cortical Responses To Pdl Stimulationsupporting
confidence: 70%
“…Early studies using neuroanatomical and electrophysiological techniques identified the dysgranular region of the IC as the gustatory cortex (Kosar et al 1986a,b). Also, in vivo intrinsic imaging experiments showed that the anterior part of the IC responded best to taste modalities (Accolla et al 2007). Further, a more recent study using neuronal activity mapping with Arc mRNA (Saddoris et al 2009) indicates that the integration of taste-related information mostly occurs in the anterior dysgranular region of the IC.…”
Section: Resultsmentioning
confidence: 99%
“…2A Left) and we conducted in vivo intrinsic optical imaging to map functional activity in the GC (Fig. 2 A Right) (13). Rats of CTA (n ϭ 8), CS-Ctrl (n ϭ 8), and US-Ctrl (n ϭ 5) groups were imaged on test day 2 (however, similar results were also obtained on TD1, n ϭ 4, data not shown) when there was a significant difference of the saccharin preference among the groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The GC therefore constitutes an ideal region to investigate sensory maps plasticity after conditioned learning. Recently, we studied the spatial representation of taste modalities in the GC (13). Taste maps differ across modalities and seem to contain also information about the pleasantness (or hedonic value) of the stimulus.…”
mentioning
confidence: 99%